2001
DOI: 10.1121/1.1417527
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of voice F0 responses to pitch-shift onset and offset conditions

Abstract: In order to maintain a steady voice fundamental frequency (F 0 ), it is assumed that people compare their auditory feedback pitch with an internal (memory) or external (acoustic) referent. In the present study we examined whether the internal referent is fixed or variable by comparing voice F 0 responses to incorrect auditory feedback in two timing conditions. In one condition, the incorrect pitch was introduced during vocalization (ON condition). In the second, the incorrect auditory feedback pitch was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
86
5
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 9 publications
10
86
5
6
Order By: Relevance
“…A minimum duration of at least 50 ms, a minimum peak time of 120 ms, a minimum magnitude of 5 cents, and a maximum latency no greater than 400 ms were required for a response to be considered valid. Previous experiments utilized similar duration criteria (Burnett et al, 1998;Burnett and Larson, 2002;Hain et al, 2000;Larson et al, 2001Larson et al, , 2000 to reduce invalid responses. Peak time, magnitude, and latency criteria were used to eliminate extreme data outliers.…”
Section: Methodsmentioning
confidence: 99%
“…A minimum duration of at least 50 ms, a minimum peak time of 120 ms, a minimum magnitude of 5 cents, and a maximum latency no greater than 400 ms were required for a response to be considered valid. Previous experiments utilized similar duration criteria (Burnett et al, 1998;Burnett and Larson, 2002;Hain et al, 2000;Larson et al, 2001Larson et al, , 2000 to reduce invalid responses. Peak time, magnitude, and latency criteria were used to eliminate extreme data outliers.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies demonstrated that masking of auditory feedback led to a deterioration in fine control of F 0 and inaccuracy in singing musical notes (Elliott and Niemoeller 1970;Mallard et al 1978;Mürbe et al 2002). Presentation of sudden perturbations in voice auditory pitch feedback while subjects are speaking or sustaining a vowel sound have demonstrated compensatory changes in voice F 0 production (Burnett et al 1998;Chen et al 2007;Donath et al 2002;Hain et al 2000;Jones and Munhall 2002;Kawahara 1995;Larson et al 2001;Natke and Kalveram 2001;Sapir et al 1983;Xu et al 2004). …”
Section: Introductionmentioning
confidence: 99%
“…First consider the case of our previous work where voice auditory pitch feedback was experimentally shifted while kinesthesia was left intact (Burnett et al 1998;Hain et al 2000;Larson et al 2001;Xu et al 2004). To the extent that kinesthetic feedback contributes to stabilization of F 0 , experimental inferences that neglect kinesthetic feedback should result in an incorrectly low estimate of the coupling between auditory error and F 0 error (F gain and F Tc in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the reflexive control of speech loudness appears to follow a time course similar to the response to pitch-shifted feedback, or the pitch-shift reflex (PSR) [4,9,49,72,73,136]. Speakers exhibit a reflexive compensatory response to perceived shifts in voice pitch which occurs with a latency of approximately 130 ms and, again, appears not to be under volitional control [4,9,72,73,136].…”
Section: Auditory Feedback In Normal and Disrupted Vocalizationsmentioning
confidence: 99%
“…Speakers exhibit a reflexive compensatory response to perceived shifts in voice pitch which occurs with a latency of approximately 130 ms and, again, appears not to be under volitional control [4,9,72,73,136]. In a related series of experiments [52], when speakers were presented with feedback in which the formant frequency of specific vowels was electronically shifted within a subset of specific words, speakers subsequently made compensatory changes in the production of the pitch-shifted vowels not only in the test words containing the altered vowel, but also in other words containing the same vowel.…”
Section: Auditory Feedback In Normal and Disrupted Vocalizationsmentioning
confidence: 99%